The vertical distribution and abundance of gastropods and bivalves from rocky beaches of Cuastecomate Bay, Jalisco. México - Esqueda, M C (2000)
The vertical distribution and abundance of conspicuous gastropod and bivalve species were studied at five rocky beaches in Cuastecomate Bay, Jalisco. Sampling was done from September, 1993 through March, 1994 with 0.75 m2 quadrants placed along replicate transect lines (10 m long) in the supralittoral and mesolittoral (upper, middle and lower intertidal) zones. A total of 6 643 mollusks were collected. Gastropods dominated the samples (6 272 individuals, 44 species); the bivalves were less abundant and diverse (371 individuals, five species). Seventeen species comprised 89.8% of all individuals collected. The gastropods Nodilittorina aspera and Nerita scabricosta were the most abundant with 637.8 and 71.43 individuals/m2, respectively. The most abundant bivalves were Brachidontes adamsianus and Chloromytilus palliopunctatus with 60.7 and 61.3 individuals/ m2 respectively. The abundance of gastropods decreased from the supralittoral to the lower tidal zones while the number of species increased in the same direction. The number of species of bivalves also increased from the supralittoral to the lower intertidal zone; the abundance of individuals was higher at the middle intertidal zone. Affinities between groups of species among sampling stations were identified by computing Pearson’s correlation coefficient using abundance values (ind./m2) and Jaccard’s dissimilarity index using species presence or absence in the lower intertidal zone. Affinity among stations was not dependent upon their vicinity but on the high dominance of few species, the occurrence of many secondary species and beach characteristics